IMPLEMENTATION OF STAD TYPE COOPERATIVE LEARNING TO IMPROVE MATHEMATICAL LEARNING OUTCOMES CLASS VIII STUDENTS - Mohammad Archi Maulyda; Umar Umar; Muhammad Erfan; Vivi Rachmatul Hidayati; Linda Feni Haryati (JIPMat, 2020)
This study aims to describe the application of STAD type cooperative learning that can improve mathematics learning outcomes of eighth-grade students of SMPN 12 Malang. This type of research is a PTK Kemmis & Mc Taggart model with qualitative consisting of two cycles. This research was conducted in class VIII-A of SMPN 12 Malang which was held by 30 students. Based on the research, STAD type cooperative learning steps are obtained that can improve mathematics learning outcomes of VIII grade students of SMPN 12 Malang, namely (1) Class presentations, teachers do apperception and encourage through question and answer and worksheets. (2) Group discussion, students work together with their groups to work on problems through worksheets. (3) Individual quizzes, students work on individual quizzes. (4) Calculation of individual improvement scores, students exchange and correct the quiz results. Quiz results are used to determine individual or student improving scores and group scores. (5) Giving awards, teachers give awards to the best groups.